+0  
 
0
46
1
avatar+52 

https://web2.0calc.com/questions/if-x-y-satisfies-the-simultaneous-equations-where

 Jul 1, 2021
 #1
avatar+120966 
+1

3xy  -4x^2 -36y  +48 x   = 0

 

3xy  - 36y  -  4x^2  +  48x  =  0

 

3y ( x - 12)    -  4x(x - 12)  =  0

 

(x - 12)  ( 3y  - 4x)   =  0

 

x =  12                  and       3y  = 4x    ⇒     y  =  (4/3)x

 

Using the  first  solution  in  the  second equation, we  have

 

x^2 - 2y^2  =  16

12^2  - 2y^2  = 16

12^2 -  16  = 2 y^2

144 - 16  = 2y^2

128   =  2y^2

64   = y^2 

y = 8    and  -8

 

So   (12, 8)  and (12 , -8)  are  solutions

 

And 

x^2  - 2  [( 4/3)x]^2  =   16

x^2  -  (32/9)x^2  =  16

(-23/9)x^2   =  16

x^2  =  16  (-9 / 23)

x^2  = -144/23

So

x = -12i / sqrt (23)         and  x =  12i / sqrt (23)

And  y  =  (4/3) (-12i) / sqrt 23   =   -16i/sqrt 23           and   16i / sqrt (23)

 

So

 

( -12i/sqrt 23, -16i/sqrt 23)   and  ( 12i/sqrt 23  , 16i/sqrt 23)     are also solutions

 

 

 

cool cool cool

 Jul 1, 2021
edited by CPhill  Jul 1, 2021

9 Online Users

avatar